Expressions of the multiple: interdisciplinary practices - Salvatori, Maristela (PORTO ARTE: Revista de Artes Visuais, 2018)
This article presents aspects of recent studies within the universe of the multiple in its various expressions in today’s world, based on projects linked to the Research Group on Expressions of the Multiple (CNPq-PPGAV/IA/UFRGS).